2014
DOI: 10.1007/s11240-014-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulators affect biosynthesis and accumulation profile of isoflavone phytoestrogens in high-productive in vitro cultures of Genista tinctoria

Abstract: The influence of plant growth regulators on biomass growth and the accumulation of medicinally-relevant isoflavone phytoestrogens, derivatives of genistein and daidzein (8 compounds including aglycones, glucosides and glucoside esters) in callus cultures of Genista tinctoria (Fabaceae) was examined. The experiments included 10 auxins [2,4-dichlorophenoxyacetic acid (2,4-D), p-chlorophenoxyacetic acid, indole-3-acetic acid, indole-3-butyric acid, indole-3-propionic acid, 1-naphthaleneacetic acid, b-naphthoxyace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Also, no positive results were found for TIBA, an anti-auxin included in the experiments because of its stimulatory effect on secondary metabolism observed in previous work by the authors (Luczkiewicz et al 2002(Luczkiewicz et al , 2014.…”
Section: Discussionmentioning
confidence: 67%
“…Also, no positive results were found for TIBA, an anti-auxin included in the experiments because of its stimulatory effect on secondary metabolism observed in previous work by the authors (Luczkiewicz et al 2002(Luczkiewicz et al , 2014.…”
Section: Discussionmentioning
confidence: 67%
“…After testing several distinct plant growth regulators in different concentrations and groups, Luczkiewicz et al (2014) also observed a higher production of isoflavones in calli of Genista tinctoria L. elicitated with cytokins.…”
Section: Improvement Of Plant Tissue Culture Through the Use Of Elicimentioning
confidence: 88%
“…Among these factors, the plant growth stage was found overwhelming the effect of plant genotype on the total bacterial communities associated with potato (van Overbeek and van Elsas, 2008 ). In addition, it has been proved that the plant growth regulators could simulate lots of physiological processes in plants and improve the plant performance (Ren et al, 2011 ; Luczkiewicz et al, 2014 ). However, little information is available about the effects of growth regulators on the endophytes associated with plant leaves.…”
Section: Introductionmentioning
confidence: 99%